2006
DOI: 10.1086/510290
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-assisted Accretion for Massive Stars

Abstract: Gravitational interactions in very young high-density stellar clusters can to some degree change the angular momentum in the circumstellar discs surrounding initially the majority of stars. However, for most stars the cluster environment alters the angular momentum only slightly. For example, in simulations of the Orion Nebula cluster (ONC) encounters reduce the angular momentum of the discs on average at most by 3-5% and in the higher density region of the Trapezium by 15-20% -still a minor loss process. Howe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…A typical example of such an environment is the Orion nebula cluster (ONC). In an earlier paper (Pfalzner 2006), we demonstrated that encounters cause a 3−5% specific angular momentum loss in the ONC, rising to 10−15% in the dense inner Trapezium region. Since specific angular momentum loss is a prerequisite for accretion, we suggested that in the final star formation stages an additional growth mechanism for massive stars exist (cluster-assisted accretion) as massive stars lose their Article published by EDP Sciences specific angular momentum to a higher degree than low-mass stars.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…A typical example of such an environment is the Orion nebula cluster (ONC). In an earlier paper (Pfalzner 2006), we demonstrated that encounters cause a 3−5% specific angular momentum loss in the ONC, rising to 10−15% in the dense inner Trapezium region. Since specific angular momentum loss is a prerequisite for accretion, we suggested that in the final star formation stages an additional growth mechanism for massive stars exist (cluster-assisted accretion) as massive stars lose their Article published by EDP Sciences specific angular momentum to a higher degree than low-mass stars.…”
Section: Introductionmentioning
confidence: 70%
“…We have combined simulations of the cluster dynamics performed with the Nbody6++ code (Spurzem 1999) with tree code simulations, to study the effect of encounters on star-disc systems as described in Pfalzner (2006). Here we determine the likelihood and degree of the encounter-triggered accretion processes.…”
Section: Methodsmentioning
confidence: 99%
“…This approach is justified by the interplay of three effects: (i) A disc-mass loss of this order lowers the density in the disc significantly, in particular in the outer parts; the disc size decreases. (ii) The accompanying angular momentum loss enhances accretion of the extant material onto the star (Pfalzner 2006). This leads temporarily to an increase of the infrared excess but soon fades after a short intense accretion phase (Pfalzner 2008, subm.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Lada & Lada 2003;Porras et al 2003;Evans et al 2009). The accretion discs of these stars are thus exposed to environmental effects that could affect their evolution (Richling & Yorke 1998;Hollenbach et al 2000;Scally & Clarke 2001;Adams et al 2004;Olczak et al 2006;Pfalzner 2006;Pfalzner et al 2006;Pfalzner & Olczak 2007;Clarke 2007;Olczak et al 2010). As these discs are the prerequisites for the formation of planetary systems this process might be influenced by the olczak@ari.uni-heidelberg.de 1 Max-Planck-Institut für Astronomie (MPIA), Königstuhl 17, 69117 Heidelberg, Germany 2 National Astronomical Observatories of China, Chinese Academy of Sciences (NAOC/CAS), 20A Datun Lu, Chaoyang District, Beijing 100012, China 3 The Kavli Institute for Astronomy and Astrophysics at Peking University (KIAA), Yi He Yuan Lu 5, Hai Dian Qu, Beijing 100871, China cluster environment.…”
Section: Introductionmentioning
confidence: 99%